2011
DOI: 10.5194/acp-11-4957-2011
|View full text |Cite
|
Sign up to set email alerts
|

Coherence of long-term stratospheric ozone vertical distribution time series used for the study of ozone recovery at a northern mid-latitude station

Abstract: Abstract. The coherence of stratospheric ozone time series retrieved from various observational records is investigated at Haute-Provence Observatory • N, 5.71 • E). The analysis is accomplished through the intercomparison of collocated ozone measurements of Light Detection and Ranging (lidar) with Solar Backscatter UltraViolet(/2) (SBUV(/2)), Stratospheric Aerosol and Gas Experiment II (SAGE II), Halogen Occultation Experiment (HALOE), Microwave Limb Sounder (MLS) on Upper Atmosphere Research Satellite (UARS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 49 publications
(51 reference statements)
1
39
0
Order By: Relevance
“…The latest version of the ozone profile algorithm for processing of Dobson Umkehr data (UMK04) is described in Petropavlovskikh et al (2005). Although Umkehr profiles show systematic biases in comparisons with other measurements (Nair et al, 2011;Kramarova et al, 2013b), this is of less concern for trend analysis when the UMK04 profile retrievals are used as monthly mean anomalies. However, smoothing errors, especially in the lower stratosphere, create low vertical resolution in the Umkehr retrieved profile and enhance retrieval noise in the lower stratosphere and troposphere.…”
Section: Dobson/brewermentioning
confidence: 99%
“…The latest version of the ozone profile algorithm for processing of Dobson Umkehr data (UMK04) is described in Petropavlovskikh et al (2005). Although Umkehr profiles show systematic biases in comparisons with other measurements (Nair et al, 2011;Kramarova et al, 2013b), this is of less concern for trend analysis when the UMK04 profile retrievals are used as monthly mean anomalies. However, smoothing errors, especially in the lower stratosphere, create low vertical resolution in the Umkehr retrieved profile and enhance retrieval noise in the lower stratosphere and troposphere.…”
Section: Dobson/brewermentioning
confidence: 99%
“…They found that zenith-sky Umkehr data from an automated Dobson spectrophotometer systematically underestimate the stratospheric ozone concentration with a near-zero bias at about 30 km, but increase to 7 % at 21 and 34 km, and to 14 % at 40 km (Fig. 8 of Nair et al, 2011). Despite these large biases, Nair et al (2011) concluded that Umkehr data are useful for studies of long-term ozone evolution and for detecting drifts in satellite observations.…”
Section: Discussionmentioning
confidence: 99%
“…9 of McElroy and Kerr, 1995). Nair et al (2011) compared stratospheric ozone vertical distribution measured by a large number of ground-based and satellite sensors at the Haute-Provence Observatory, France. They found that zenith-sky Umkehr data from an automated Dobson spectrophotometer systematically underestimate the stratospheric ozone concentration with a near-zero bias at about 30 km, but increase to 7 % at 21 and 34 km, and to 14 % at 40 km (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its drift, i.e., the long-term measurement stability, should be quantitatively assessed with independent instruments. Ground-based ozone lidar is a potential candidate for such purposes and can be used to estimate drift (e.g., Nair et al, 2011Nair et al, , 2012Eckert et al, 2014;Hubert et al, 2016). Hubert et al (2016) comprehensively evaluated the bias and drift of 14 limb-viewing satellite sensors using ozonesonde and ozone lidar measurements.…”
mentioning
confidence: 99%